Mali : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2013)
Mali's Growth and Poverty Reduction Strategic Paper provides a comprehensive framework for implementing an ambitious growth and poverty reduction agenda. Executive Directors approve the elaboration of GPRSP-3, which will guide the country in its efforts to sustainably reduce poverty. The strategy is both comprehensive and ambitious, and the approach to integrate short-term crisis-related programs within the medium term GPRSP-3 framework is commended. However, the successful implementation hinges critically on full political support and commitment to address key shortcomings.